2017
DOI: 10.1021/acssuschemeng.7b02770
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Delivery of Homogeneous Fluorous Rhodium Catalysts Using Poly(tetrafluoroethylene): “Catalyst-on-a-Tape”

Abstract: The red−orange fluorous rhodium(I) complexes ClRh(P((CH 2 ) m R fn ) 3 ) 3 (m/n = 2/6 (1a), 2/8, 3/6, 3/ 10; R fn = (CF 2 ) n−1 CF 3 ) are essentially insoluble in organic solvents at 20 °C but have measurable solubilities in dibutyl ether at 55−65 °C. Under these conditions, they are effective catalyst precursors for the hydrosilylation of cyclohexanone by PhMe 2 SiH. Upon cooling, the catalyst rest states precipitate, giving colorless solutions of C 6 H 11 OSiPhMe 2 . When this sequence is conducted in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 83 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Rh is regarded as an important active center, which is widely applied in various syntheses and their catalysis. In numerous syntheses, it has been used as a catalyst for cyclopropanation, , hydroformylation, , and C–H bond activation; , what is more, it has also been used for manufacturing acetic acid and β2-amino acid . In particular, Shan et al reported a mononuclear rhodium species, which was anchored on a zeolite or titanium dioxide support suspended in an aqueous solution; they catalyzed the direct conversion of methane to methanol and acetic acid using oxygen and carbon monoxide under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Rh is regarded as an important active center, which is widely applied in various syntheses and their catalysis. In numerous syntheses, it has been used as a catalyst for cyclopropanation, , hydroformylation, , and C–H bond activation; , what is more, it has also been used for manufacturing acetic acid and β2-amino acid . In particular, Shan et al reported a mononuclear rhodium species, which was anchored on a zeolite or titanium dioxide support suspended in an aqueous solution; they catalyzed the direct conversion of methane to methanol and acetic acid using oxygen and carbon monoxide under mild conditions.…”
Section: Introductionmentioning
confidence: 99%